Salvator rufescens (Argentine Red Tegu): Diet - Castillo, Gabriel Natalio (2018)
Salvator refescens is one of the largest lizards in South America, distributed in Argentina, Bolivia, Paraguay, and Brazil (Montero et al. 2004. Cuad. Herpetol. 18:17–32; Cabrera 2009. Lagartos del Centro de la Argentina. Fundación de Historia Natural, Córdoba, Argentina. 120 pp.). It is mainly omnivorous, feeding on a diversity of prey (Williams et al. 1993. Neotrópica 39:45–41; Lopez Juri et al. 2015. South Am. J. Herpetol. 10:132–142). Herein we describe new dietary items for S. rufescens.